Hubungan Preeklamsia dengan Kejadian Bayi Berat Lahir Rendah - Primadevi, Inggit; Susanti, Riska Umi (Ners Akademika, 2022)
Purpose: The research objective was to determine whether preeclampsia in pregnant women is correlate with the genesis of low birth weight at the Batin Mangunang Regional General Hospital in Tanggamus Regency 2020. Method: This type of quantitative research with a cross-sectional design, the population in this research were all mothers giving birth with preeclampsia at the Batin Mangunang Regional General Hospital in 2020, with a case sample of 70 patients. The analysis used univariate and bivariate by using Chi Square test. Results: From the results of the research, it is known that the frequency distribution shows that 9 babies with LBW or 56.2% of all LBW babies were born to mothers with severe preeclampsia, and only 7 babies with LBW or as many as 43.8% were born to mothers who gave birth with mild preeclampsia. Meanwhile, 77.8% of infants without LBW were born to mothers with mild preeclampsia, and only 22.2% of non-LBW babies were born to mothers with severe preeclampsia. The results of data processing resulted in p value = 0.014, it can be concluded that there is a significant correlation between preeclampsia and low birth weight babies at the Batin Mangunang Regional General Hospital in Tanggamus Regency 2020. Contribution: The results of this research are expected to be used as evaluation material to improve midwifery services and improve quality services, especially for pregnant women with the incidence of preeclampsia and LBW.